2010
DOI: 10.1111/j.1865-1682.2010.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study on Foot-and-Mouth Disease in Cattle: Seroprevalence and Risk Factor Assessment in South Omo Zone, South-western Ethiopia

Abstract: A cross-sectional sero-epidemiological study was conducted in seven districts of the South Omo zone, south-western Ethiopia, between October 2008 and May 2009 with the objective of determining the seroprevalence of foot-and-mouth disease (FMD) in cattle and identifying the potential risk factors associated with the disease. In total, 770 cattle sera samples were collected and submitted to the National Veterinary Institute (NVI), Debre Zeit, Ethiopia, for screening using the 3ABC-ELISA. The overall seroprevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
42
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 11 publications
10
42
7
Order By: Relevance
“…This study is in agreement with other studies which reported that the movement of herds in search of pasture and water from one area to another is a significant risk factor for the occurrence of FMD (Habiela et al, 2010;Molla et al, 2009;Megersa et al, 2009).Herds that reported mixing at the watering point with other herds recorded the highest seroprevalence relative to those that do not mix with other herds. Watering point was observed to be a common place where cattle of different herds meet in search of water, thereby serving as foci of FMD transmission.…”
Section: Discussionsupporting
confidence: 82%
“…This study is in agreement with other studies which reported that the movement of herds in search of pasture and water from one area to another is a significant risk factor for the occurrence of FMD (Habiela et al, 2010;Molla et al, 2009;Megersa et al, 2009).Herds that reported mixing at the watering point with other herds recorded the highest seroprevalence relative to those that do not mix with other herds. Watering point was observed to be a common place where cattle of different herds meet in search of water, thereby serving as foci of FMD transmission.…”
Section: Discussionsupporting
confidence: 82%
“…However, the seroprevalence was slightly lower than the previous findings in Ethiopia (Sahle, 2004) in which a seropositivity of 26.5% was reported. On the contrary, the seropositivity found in current study was higher than the report in Afar Regional State where seropositivity of 5.6% (Jembere, 2008) and in South Omo Zone where seropositivity of 8.18% was reported (Molla et al, 2010). The relative increase in the prevalence of the FMD in comparison to other findings might be due to extensive livestock movement and high rate of contact at market place, grazing and watering points which are potential risk factors for the transmission of the disease in the study area.…”
Section: Discussioncontrasting
confidence: 56%
“…Studies undertaken on FMD so far revealed the existence of the disease in different parts of the country, with prevalence that vary from 8.18% in south Omo (Molla et al, 2010) to 44.2% in different parts of the country (Negusssie et al, 2010) and posing a major threat to cattle in many parts of the country, thereby causing considerable economic losses through morbidity, mortality and trade restriction.…”
Section: Introductionmentioning
confidence: 99%